Risk of Obstructive Sleep Apnea in Pregnancy by STOP-BANG Questionnaire - Abolhasan Halvani; Maasoumeh Barkhordari-Sharifabad; Azizeh Ghane-Ezabadi; Abdolhossein Alimohammadi-Kamalabadi (پزشکی بالینی ابن سینا, 2022)
Background and Objective: Obstructive Sleep Apnea Syndrome (OSAS) is common during pregnancy and is associated with adverse maternal and fetal outcomes, including hypertension, preeclampsia, and low birth weight; therefore, screening pregnant women is of particular importance. This study aimed to assess OSAS risk during pregnancy in women referring to health centers in Yazd city, Iran. Materials and Methods: In this cross-sectional study, 400 pregnant women, who referred to Yazd health centers in 2020, were included in the study. Data collection tools included a demographic form and the STOP-BANG questionnaire to determine OSAS risk. The data were analyzed in SPSS software (version 16) using descriptive and inferential statistics and considering the significance level of 0.05. Results: The mean scores of the participants' age and body mass index (BMI) were obtained at 28.44±5.74 years and 27.31±5.28 kg/m2, respectively. The frequency rates of diabetes and hypertension were 8% and 3.3%, respectively. It was found that 94.5% of the women were at low risk of OSAS, while 2.5% and 3% of them were at moderate and high risk, respectively. There was no association between diabetes and OSAS risk (P>0.05); however, a history of hypertension, BMI above 30 kg/m2, and age over 30 years were associated with increased OSAS risk and higher STOP-BANG score (P<0.05). Conclusion: The STOP-BANG questionnaire is a simple tool for screening OSAS in pregnant women. Age over 30, BMI over 30 kg/m2, and a history of hypertension were associated with higher STOP-BANG scores; therefore, pregnant women with these characteristics are at higher risk for developing OSAS and are a higher priority for screening than other groups.